ANALISIS UNSUR INSTRINSIK DALAM CERPEN BERJUDUL “SETANGKAI POHON IBU” KARYA VAUGHAN CALLISTA, V.P - NIA, IKA; SUDRAJAT, ROCHMAT TRI; -, LATIFAH (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The short story is a fictional narrative with a length of about 500 to 10,000 words and is more focused than a novelet, short stories tend to be short, mostly only telling a single incident, but still paying attention to the elements in it such as themes, characters, plot, background, characterization, message and style of language. The short story "Setangkai Pohon Ibu" by Vaughan Calista, V.P is a literary work that has a message and a useful moral message, and can be used as an appropriate reading source for readers. The formulation of the problem in this study is how to analyze the intrinsic elements contained in the short story? And what mandate can we take in the short story, so that we can draw the final conclusion of the short story. The purpose of this study was to determine the theme, plot, setting, characterization, point of view and mandate in the short story "Setangkai Pohon Ibu" by Vaughan Callista, V.P. The method used in this research is descriptive method, in which data is decomposed in the form of words or pictures, not in the form of numbers. This research form uses a structural approach. The short story "Set a Ibu Pohon" by Vaughan Callista, VP with the theme of love, the characters involved are Daniel, mother, and father, the plot used by the writer is a forward plot with a background where it refers to the hospital, garden, Daniel's room, the time setting shows morning. days, an atmosphere of tension, sadness and happiness. The point of view used is the third person pronoun, as for the mandate contained in a short story "A Mother's Tree" is that we must always keep nature in order to keep it beautiful by guarding the trees and not cutting it carelessly, because by protecting nature, it will be very many benefits to our future